Demographical risk factors of adverse events following immunisation of CoronaVac in Jambi, Indonesia - Heriyanto, Rivaldo; Yanto, Theo Audi; Octavius, Gilbert Sterling; Nisa, Haviza; Ienawi, Catherine; Pasai, Emildan (Universitas Udayana, 2023)
Background and purpose: Slow uptake of COVID-19 vaccination might be associated with the adverse events after vaccination. This study aims to evaluate the association between demographical factors and COVID-19 vaccine adverse events in Jambi, Indonesia Methods: We conducted a cross-sectional study with a total population sampling. Data were collected with a structured questionnaire. We included adults vaccinated for the first dose with CoronaVac in Putri Ayu Public Health Center between March 15th and June 3rd, 2021, accounted for 522 persons. Statistical analysis was done using IBM SPSS 26.0. Multivariate logistic regression analysis was used to analyze the predictive models. Results: This Out of 522 respondents included, immune reactions (34.1%) were the most common adverse effects reported by the respondents. Multivariate analysis showed that respondents with no family members or friends exposed to COVID-19 are less likely to experience puncture site reaction with an OR of 0.28 (95%CI: 0.09-0.92; p=0.036). Those with no history of mental disorders were also less likely to experience the adverse event with an OR of 0.12 (95%CI: 0.024-0.62; p=0.011). As for other reactions, those in the 26-35 years old category are more likely to experience other adverse event reactions with an OR of 11.62 (95%CI: 1.5-89.92; p=0.019). Conclusion: Based Younger respondents tend to experience more other reaction of COVID-19 vaccine adverse events than the older groups. We also found that those with no family or friends who contracted COVID-19 and no history of mental disorders are less likely to experience puncture site reaction adverse events.